2021
DOI: 10.1155/2021/6635704
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of False-Negative Early Gastric Cancers: A Retrospective Study of Endoscopic Submucosal Dissection Cases

Abstract: Background. We frequently encounter early gastric cancer (EGC) that could not be detected in the previous esophagogastroduodenoscopy even if the procedure was annually performed. However, little evidence exists regarding the characteristics of false-negative EGCs. Our aim was to reveal the clinical features of false-negative EGCs. Methods. We retrospectively reviewed cases of endoscopic submucosal dissection (ESD) for EGCs in Fukuchiyama City Hospital between January 2013 and May 2019. False-negative EGCs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Reported detection and missed rates of gastric neoplasm for trainees are not significantly different than those for experienced endoscopists,22–25 even though endoscopic training and education were essential ways to increase the GC detection 26 27. Our study had similar findings: the observed GC detection rates in routine EGDs bore no relation to whether the endoscopists were trainees or experienced, board-certified endoscopists.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Reported detection and missed rates of gastric neoplasm for trainees are not significantly different than those for experienced endoscopists,22–25 even though endoscopic training and education were essential ways to increase the GC detection 26 27. Our study had similar findings: the observed GC detection rates in routine EGDs bore no relation to whether the endoscopists were trainees or experienced, board-certified endoscopists.…”
Section: Discussionsupporting
confidence: 56%
“…Reported detection and missed rates of gastric neoplasm for trainees are not significantly different than those for experienced endoscopists, [22][23][24][25] even though endoscopic training and education were essential ways to increase the GC detection. 26 27 Our study had similar findings: the observed GC detection rates in routine Since the endoscopists with the highest and lowest detection rates (2.87% and 0.09%) were so far removed from the detection rates of the other endoscopists, we excluded those data as outliers from this comparative analysis.…”
Section: Discussionmentioning
confidence: 96%
“…Studies have shown that HP eradication conceals the findings of early cancer lesions, which may lead to a delayed cancer diagnosis [7][8][9][10]24]. Moreover, two previous studies demonstrated that this concern could be a real issue by showing that post-eradicated GC showed a higher proportion of submucosal invasion than cases of HP-positive GC [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Still, HP eradication was not significantly associated with GCs with deep tumor invasion, even after adjusting for such cancer lesion-related factors, suggesting that the effect of HP eradication does not predispose one to develop GC with deep tumor invasion. As studies have demonstrated, HP eradication may make it difficult to diagnose early-stage GC by obscuring the characteristic lesions [7][8][9][10]24]. At the same time, other studies demonstrated that HP eradication decreased the proliferation of GC [7,25], suggesting that the growth of neoplastic lesions was decelerated in HP-eradicated cases [21,[26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Optimal mucosal visualisation should be obtained through a combination of air insufflation, aspiration and the use of mucosal cleansing techniques with mucolytic and defoaming agents (e.g., N -acetylcysteine and simethicone) [ 157 ], see Figure 8 , Figure 9 , Figure 10 , Figure 11 , Figure 12 , Figure 13 , Figure 14 . Despite progress made to date, premalignant lesions and early gastric cancer are still being missed [ 191 , 192 ]. A meta-analysis of 22 studies estimated a rate of missed gastric cancer at endoscopy of 9.4% [ 193 ].…”
Section: Optimal Endoscopy Setting For Detection Of An Early Gastric Neoplasiamentioning
confidence: 99%